19. PERAN ASEAN CONVENTION ON COUNTER TERRORISM DALAM PENANGANAN TERORISME DI FILIPINA PERIODE 2011 – 2013 - Namora, Giuliani Agustha; Windiani, Reni; Paramasatya, Satwika (Journal of International Relations, 2016)
The terrorist attack that happened in various states particularly after 9/11 tragedy is not anew issue for the Southeast Asian countries. The issue of terrorism that was once became aconcern of individual country, has now became a shared concern for the countriesinSoutheast Asia due to the situation in the international order that are facing complexsecurity. Various acts of terrorist attack that hasoccurred in the Philippines arethe concreteexample of the complex security, because the terrorist groupsfrom the rest of the SoutheastAsian countries itself are linkedto each other. ASEAN as an institution representing theSoutheast Asia region issued the ASEAN Convention on Counter Terrorism in 2007 as aresponse to the threats of terrorism faced by the region. This research aims to analyze therole of ACCT convention in combating terrorism in the Phlippines in the year 2011 – 2013due to the increasing number of terrorist attack since the convention came into force. Toanalyze the role itself, this research uses neoliberal institutionalism theory. The methodthat is used in this research is qualitative method with descriptive-analytical type throughinterviews and literature technics. Outcome from this research is the ACCT Conventionhas role in providing legal norms, ordinances, and strategies in facing terrorist threats tothe member countries of ASEAN. These strategies had been implemented by thePhilippines through various actions and activities during the year 2011 – 2013 such as theadoption of new laws related to terrorism, provision of capacity building training for lawenforcement and counter-radicalization or rehabilitation programs for former perpetratorsof terrorism.